2022
DOI: 10.2174/2772434417666220902153823
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Efficacy in the Management of Mild to Moderate Hospitalized COVID-19: A Pilot Randomized Triple-blind Placebo- controlled Clinical Trial

Abstract: Background: Statins are first-line lipid-lowering agents with tolerable adverse reactions, low cost, and high availability worldwide. The potent anti-inflammatory, antioxidant, anti-thrombotic and immunomodulatory effects of statins propose them as an option to face COVID-19 infection. Objective: In this randomized triple-blind placebo-controlled clinical trial, we have investigated the atorvastatin efficacy in the management of mild to moderate hospitalized COVID-19 patients. Methods: In this study, 52 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Consistently, there is no clear evidence regarding the protective effects of in-hospital statin therapy (either continuation or introduction de novo) on the most severe forms of COVID-19. 13,14,[18][19][20][21]32,[45][46][47] Thus, as to whether statin-mediated protective effects in the context of COVID-19 may be time-…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistently, there is no clear evidence regarding the protective effects of in-hospital statin therapy (either continuation or introduction de novo) on the most severe forms of COVID-19. 13,14,[18][19][20][21]32,[45][46][47] Thus, as to whether statin-mediated protective effects in the context of COVID-19 may be time-…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the exploratory analyses of the present study, statin continuation during hospitalization was not associated with COVID‐19 outcomes. Consistently, there is no clear evidence regarding the protective effects of in‐hospital statin therapy (either continuation or introduction de novo) on the most severe forms of COVID‐19 13,14,18–21,32,45–47 . Thus, as to whether statin‐mediated protective effects in the context of COVID‐19 may be time‐dependent remains an open issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 24 observational studies have reported similar results [ 26 , 158 , 169 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 ]. The results of six RCTs of inpatient statin treatment have also been reported [ 199 , 200 , 201 , 202 , 203 , 204 ]. All of these results are summarized in Table 4 .…”
Section: Inpatient Statin Treatmentmentioning
confidence: 99%
“…The relative risk of death was 0.90 (95% CI = 0.73–1.11; p value = 0.33). Daily statin treatment had no effect on mortality, but three of the six studies were very small [ 199 , 200 , 204 ], four used what was probably too low a dose of atorvastatin (20 mg instead of 40 mg) [ 199 , 200 , 201 , 202 ], and one dealt only with ICU patients [ 202 ], which may have been too late in the course of illness. Two RCTs examined simultaneous treatment with several drugs [ 200 , 203 ].…”
Section: Inpatient Statin Treatmentmentioning
confidence: 99%